Effect of microbial‐based inoculants on nutrient concentrations and early root morphology of corn (Zea mays) - Calvo, Pamela; Watts, Dexter B.; Kloepper, Joseph W.; Torbert, H. Allen (Journal of plant nutrition and soil science, 2017)
Microbial‐based inoculants have been reported to stimulate plant growth and nutrient uptake. However, their effect may vary depending on the growth stage when evaluated or fertilizer applied. Thus, the objective of this study was to test the hypothesis that microbial‐based inoculants known to promote root growth and nutrient uptake will promote plant growth, enhance early root development, and increase nutrient concentrations of corn (Zea mays L.). Plants were evaluated at four different growth stages and in the presence of three different nitrogen (N) fertilizers. The microbial‐based treatments evaluated were: SoilBuilder™ (SB), a filtered metabolite extract of SoilBuilder™ (SBF), a mixture of four strains of plant growth‐promoting Bacillus spp (BM), and a water‐inoculated control. The experiment also included four fertilizer treatments: urea (U), urea‐ammonium nitrate (UAN), calcium‐ammonium nitrate (CAN), and an unfertilized control. Corn plants were evaluated at growth stages V2, V4, V6, and VT. Plant growth parameters for biomass, height, and SPAD readings were enhanced by the three microbial‐based treatments. A greater effect of microbial‐based treatments was observed when plants were evaluated at V6 and VT stages. Parameters of early root development such as total root length (TRL), root surface area (RSA), and length of fine roots were enhanced when microbial‐based treatments were applied. Concentrations of N, P, and K were also increased by microbial‐based treatments compared to the non‐inoculated control. Increases in plant N concentration due to microbial‐based treatments were on average 72% for CAN, 61% for UAN, 72% for urea, and 54% for the unfertilized control. Phosphorus concentration was increased most (138%) when BM was applied with CAN. In the same way, when CAN was present, K concentration was increased by 95% with BM and 65% when SB and SBF were applied. Overall, the results demonstrate that microbial‐based inoculants evaluated in this study can positively impact corn growth and nutrient concentration, especially during the late vegetative stages. Furthermore, the results indicate that the enhancement of nutrient concentrations (N, P, and K) in this case was related to the capacity of microbial‐based treatments to impact root morphology at early stages of corn growth.